EL PAISAJE RURAL DE LOS MODELOS DE PLANIFICACIÓN Y GESTIÓN - Martínez Martínez, Guadalupe (1999)
Researches about landscape constitute a fundamental contribution to planning and rural development. It reflects about the necessity to integrate to the researches the contributions of the community who live and transform the rural landscape. The participating approach allow to see how the setters perceive and y project to the future the space where they are developing. The participating processes allow to elaborate rural development programs with the settlers, paying attention to their necessities and requests.